Twenty years of amyloid arthropathy research in chickens. Issue 3 (1st September 2016) - Blanco, A.E.; Barz, M.; Icken, W.; Cavero, D.; Mazaheri, A.; Voss, M.; Schmutz, M.; Preisinger, R.
Abstract : AA amyloidosis (AAA) is a disease known as amyloid arthropathy in chicken, which represents substantial economic losses, in addition to welfare concerns. Enterococcus faecalis ( E. faecalis ) is the major pathogen found in field outbreaks of amyloid arthropathy and its specific association with this disease has been extensively confirmed. The following review discusses the sequence types of E. faecalis associated with AAA that have been identified and characterised both poultry and humans and provide different hypotheses and theories about pathogenesis and transmission of this disease. This article covers the pathology both in field and induced cases of avian amyloidosis and concludes with approaches for a possible treatment, needs for further research and future perspectives. This paper is a consolidation of current knowledge on AAA in chickens which has been obtained over the last twenty years.